Números perfeitos - Cruz, Sívio Orleans (2013)
In this thesis we study some topics of the Theory of Numbers as an inspiration for future studies of Perfect Numbers and Mersenne Primes. We present some important results for our study and analyze some statements of Fermat's Little Theorem, showing the various mathematical demonstrations that proved under various logical aspects. We have clari ed some historical aspects and conjectures for perfect numbers, through a simple narrative of facts and this will certainly give us the emphasis that have motivated and still motivates many mathematicians for the study of Perfect Numbers.